Synthesis and characterization of 3,6-O,O’- dimyristoyl chitosan micelles for oral delivery of paclitaxel - Silva, Daniella S.; Almeida, Andreia; Prezotti, Fabíola [UNESP]; Cury, Beatriz [UNESP]; Campana-Filho, Sérgio P.; Sarmento, Bruno (Elsevier, 2017)
The aim of the present study was to investigate the potential application of 3,6-O,O’- dimyristoyl chitosan DMCh, an amphiphilic derivative of chitosan, for improving the oral bioavailability of paclitaxel (PTX), a water insoluble anticancer drug. The O-acylation of chitosan with myristoyl chloride was carried out by employing high (≈13.3) or low (2.0) molar excess of chitosan to result in samples DMCh07 and DMCh12, respectively. The successful O-acylation of chitosan was confirmed by FTIR and 1H NMR spectroscopy, the latter allowing also the determination of average degree of substitution (DS). The critical aggregation concentration (CAC) of samples DMCh07 (DS ≈ 6.8%) and DMCh12 (DS ≈ 12.0%) were 8.9 × 10−3 mg/mL and 13.2 × 103 mg/mL, respectively. It was observed by TEM that the DMCh micelles showed spherical shape while DLS measurements allowed the determination of their average size (287 nm–490 nm) and zeta potential (+32 mV to +44 mV). Such DMCh micelles were able to encapsulate paclitaxel with high drug encapsulation efficiency (EE), as confirmed by HPLC analyses. Studies on the cytotoxicity of DMCh07 micelles toward Caco-2 and HT29-MTX cells showed that, regardless the PTX loaded, DMCh07 micelles slightly decreased cellular viability at low micelles concentration (≤1 μg/mL) while at high concentration (>10 μg/mL) PTX-loaded DMCh07 micelles were less toxic toward Caco-2 cells when compared to free PTX. The PTX permeation across Caco-2 monoculture and Caco-2/HT29-MTX co-culture model confirmed the potential of DMCh micelles in improving the intestinal absorption of PTX. These results suggest that DMCh micelles may be a promising carrier to encapsulate PTX aiming cancer therapy.
Keywords: Amphiphilic; Chitosan; Drug delivery; Paclitaxel; Polymeric micelles